2014
DOI: 10.12691/ajssm-2-3-4
|View full text |Cite
|
Sign up to set email alerts
|

Hydration Habits of Elite Field Futsal Players during Official Matches: Defenders and Forwards

Abstract: Futsal is a variant of soccer that is played on a smaller playing surface and mainly indoors. Futsal is played between two teams of five players, and unlimited substitutions per team are permitted. The purpose of this study has been to determine and to compare hydration habits and level of dehydration in elite futsal players during competition in relation to playing position. 4 defenders (DF) and 5 forwards (FW) were studied during 3 official matches (22-26 ºC and relative humidity 32-42.33%) in the Spanish Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
(54 reference statements)
1
2
0
Order By: Relevance
“…In agreement with previous research 11,20 , athletes in the current study were able to replace enough fluids to prevent significant dehydration, although mild dehydration was still seen occasionally. The lack of improvement in BM changes after the intervention was likely due to the fact that many participants had adequate hydration prior to the intervention.…”
Section: O N L I N E F I R S Tsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous research 11,20 , athletes in the current study were able to replace enough fluids to prevent significant dehydration, although mild dehydration was still seen occasionally. The lack of improvement in BM changes after the intervention was likely due to the fact that many participants had adequate hydration prior to the intervention.…”
Section: O N L I N E F I R S Tsupporting
confidence: 93%
“…[15][16][17][18] The few studies that have assessed indoor athletes have also shown that sweat rates are high and dehydration is still prevalent. 11,20,21 This has been found to be especially true in basketball players because of its intermittent nature. 21,22 Research on volleyball players is limited; the only study examining volleyball players' hydration status utilized adolescents athletes in a non-airconditioned facility.…”
Section: Introductionmentioning
confidence: 99%
“…Hence intensive research on knowing the game has been conducted for several years. Somatic determinants [29,30,31,32,33], physiological-motor [34,35,36,37,38,39,40,41], psychological [42,43,44,45,46] as well as technical and tactical performance [47,48,49,50,51] have already been studied. The efficiency futsal players' game has been studied, among others by Silva et al [29], Panfil and Paluszek [52], Szwarc [2], Irokawa et al [53], Leite [54], as well as Aires [55], Da Silva et al [56], Buraczewski [57], Travasson [58], Vilar [59], Gomez [60], Noel [61], Lapresa et al [62] and Sarmento et al [63].…”
Section: Introductionmentioning
confidence: 99%